Rebuilding Ukraine: How the EU should support Ukraine's reconstruction and recovery - Julian Bergmann; Iulian Romanyshyn (German Institute of Development and Sustainability (IDOS), 2022)
Russia's brutal war against Ukraine has disastrous consequences for the country. Although an end to the war is currently not in sight, it is already clear that a huge international effort will be required to support Ukraine's reconstruction. At the Ukraine Recovery Conference in July, the Ukrainian government presented a National Recovery Plan that envisions a deep modernisation of the country. The Ukrainian government's reconstruction priorities are well in sync with the European Union's (EU) ambition to promote Ukraine's transformation towards an EU member state and to foster the country's green and digital transition. The National Recovery Plan fully embraces the "build back better" principle and closely aligns the reconstruction plans with the EU's norms and standards. The EU, on its part, is willing to bear a major share of the international effort required for Ukraine's recovery. However, the same degree of unity and resolve that the EU showed when forging its initial response to the war will be needed to realise a strong EU leadership role in supporting Ukraine's long-term reconstruction. To provide a sustainable basis for Ukraine's recovery, the EU and member states need to combine ad hoc humanitarian assistance with predictable, long-term support for reconstruction. In doing so, they should consider the following key recommendations: Adopt a two-phase approach to reconstruction. The modernisation and transformation of Ukraine towards an EU member state will take several years. At the same time, the vast infrastructure losses that Ukraine is currently facing need to be addressed urgently, ideally before the winter sets in. Hence, international donors should prioritise the reconstruction of infrastructure related to basic needs, including schools, hospitals, housing, electricity grids and roads. In a second phase, deeper modernisation efforts and institutional reforms that are of relevance for eventual accession to the EU should follow. Set up adequate governance mechanisms for the joint management and oversight of reconstruction efforts. The Ukrainian government and the EU should set up a coordination platform that also involves other international partners and Ukrainian civil society actors. This platform should then develop institutional governance mechanisms for the management and oversight of projects, and ensure close coordination between the Ukrainian government and international partners. Negotiate a comprehensive agreement on the EU's contribution to the reconstruction of Ukraine. A timely agreement on the governance and funding of the EU's long-term assistance to Ukraine is needed. A mixed strategy that includes borrowing capital on behalf of the EU on the markets and funnelling additional contributions by member states to the EU's budget might be a potential way forward. In addition, the EU should swiftly examine legal possibilities to channel sanctioned Russian assets towards Ukraine's recovery. Continue and expand military assistance to Ukraine. Substantive investments in Ukraine's reconstruction should not come at the expense of necessary military aid. One priority should be to strengthen Ukraine's ability to protect its skies against Russian missile attacks. Moreover, the EU should realise its plans for an EU military training mission, provided that it creates real added value to existing efforts and matches Ukrainian needs.
Keywords: 320; Ukraine; European Union; EU foreign policy; Russia's war in Ukraine; Ukraine's reconstruction; development assistance; humanitarian aid; macro-financial assistance; European Peace Facility